An increase of larval rearing temperature does not affect the susceptibility of Phlebotomus sergenti to Leishmania tropica but effectively eliminates the gregarine Psychodiella sergenti. Issue 1 (December 2016) - Jancarova, Magdalena; Hlavacova, Jana; Votypka, Jan; Volf, Petr
Abstract Background In mosquitoes, it has previously been shown that rearing conditions of immature stages have an effect on the vector competence of adults. Here, we studied the impact of different larval rearing temperatures (27 °Cversus 32 °C) on the sand flyPhlebotomus sergenti Parrot, 1917 and its susceptibility to two parasites:Leishmania tropica Wright, 1903, a dixenous trypanosomatid transmissible from sand flies to humans, andPsychodiella sergenti Lantova, Volf & Votypka, 2010, a monoxenous sand fly gregarine. Results Increased rearing temperature (32 °C) affected the larval developmental times and size ofP. sergenti adults but had no effect on the susceptibility ofP. sergenti toL. tropica . No differences were found inLeishmania infection rates or in the intensities ofLeishmania infection. Interestingly, increased larval rearing temperature significantly suppressed the development of gregarines. All 117 control sand flies tested were infected withPs. sergenti, and the mean number of gamonts per individual was 29.5. In contrast, only three of 120 sand flies maintained at 32 °C were infected and the mean number of gamonts per individual was just 0.04. Conclusions We demonstrated that the increased rearing temperature ofP. sergenti larvae had no impact on the development ofL. tropica in adult sand flies but had a profound effect on the gregarinePs. sergenti . We suggest that increasing the larval rearing temperature by 5 °C is a simple and effective way to clean sand fly colonies infected by gregarines.